Solar Technology And Implementations in Malaysia: A Review - Prayun, Wirun; Tan, Chee Wei; Lim, Cheng Siong; Mohamad @ Abd Rahman, Syahrul Hisham; Gan, Chin Kim; Goh, Joon Sern (AENSI, 2013)
Over the years, the depleting non-renewable and increasing price of fossil fuels has encouraged growing interest in renewable energy (RE) sources. This paper presents the growth of solar or photovoltaic (PV) energy technology, implementations and its prospect particularly in Malaysia. The tropical weather of Malaysia with sunshine throughout the year increases the potential of the PV generation. PV systems can either be stand-alone or grid-connected systems. Besides that, PV systems can also be integrated with battery storage for backup purpose or export the excess electricity back to the grid. Although the PV technology has high potential to become the major source of electricity in the future, the investment of this technology is still high for which it remains as the major concern in the choice of PV energy generation option in Malaysia. In addition, the government has come out with renewable energy policy to support the generation of PV energy which has significantly increase the growth of PV deployment and PV industry in Malaysia.